2015
DOI: 10.1590/1677-3225v14n3a15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface topography and chemical composition of mini-implants

Abstract: Aim: To assess the surface topography and chemical composition of three brands of as-received mini-implants (SIN ® , Morelli ® , and Conexao ®). Methods: Twelve mini-implants of each brand were analyzed by scanning electron microscopy and energy dispersive X-ray (EDX). Results: There was no significant differences among SIN ® , Morelli ® , and Conexao ® mini-implants comparing their surface topography by visualization of SEM micrographs and analysis of scores. The EDX analysis showed statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The higher percentage of oxygen in the retrieved group could be attributed to the atmospheric oxygen exposure of the miniscrew surface during insertion/removal [2]. The higher oxygen content is proof of the oxidation process that has occurred on the implant surface which is an indication of the increased corrosion rate of the retrieved miniscrew group.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The higher percentage of oxygen in the retrieved group could be attributed to the atmospheric oxygen exposure of the miniscrew surface during insertion/removal [2]. The higher oxygen content is proof of the oxidation process that has occurred on the implant surface which is an indication of the increased corrosion rate of the retrieved miniscrew group.…”
Section: Discussionmentioning
confidence: 91%
“…The presence of nitrogen on the surface implies that proteins were adsorbed from body fluids. In a study conducted by Knop et al [2], 1.59% of nitrogen was found on a miniscrew surface. Morra et al [28] suggested that nitrogen contamination is the result of inadequate surface treatment or implant handling The source of calcium on the surface of the retrieved miniscrews could be from the contact of the miniscrew surface with blood involving mainly adsorption of proteinaceous integuments, which are calcified later with the precipitation of calcium [29].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These devices are widely used in Orthodontics offering excellent results and solving anchorage problems that could not be addressed previously. [9] Despite all the advantages of the miniimplants, there is a small present of the placed mini-implants show failure and loosening due to inaccurate bone support for mechanical retention or fracture during their removal [1] . The fracture may be due to partial osteointegration of mini-screw when left in contact with bone for a long period or due to roughness of the surface that promote osteointegration of bone on the surface of the mini-screw.…”
Section: Introductionmentioning
confidence: 99%
“…TAD body parts come into contact with the alveolar bone and ensure the stability of the mini-screw. It is essential that the structural and mechanical properties are maintained until the TADs are removed [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%